“La restricción de derechos ciudadanos para deudores de alimentos hasta los 90 días por reincidencia, prevaleciendo los derechos del alimentado” - Obando Moreira, Yenifer Estefanía (2024)
The curricular research work entitled: "Citizens' rights restriction for maintenance debtors up to 90 days, prevailing fed rights ", begins with the need to develop an analysis due to rights violation to receive food by one of the parents who is paying food through the Single System of Alimony is evidenced. Rights violation of the person being fed occurs when the provider is in arrears with the payments consecutively and is thus a recidivist in canceling. The study showed that children and adolescents rights are not being guaranteed the right to receive food , according to Judiciary Council page, the list of monthly food debtors is a very extensive in arrears in the country, This right is being violated is recognized by Republic Constitution, therefore, it is sought to put into action the most relevant principle of child enjoying this right and other fundamental rights required by fed, thus, ensuring a quality of life for the development of his person. The current Curricular Integration Work was used materials application and methods helping the right development. Moreover, surveys were conducted to legal professionals and those parents who have been affected by the non-payment of alimony; interviews were conducted only to legal professionals serving criteria to be able to propose the development of the proposed guidelines with the aim of guaranteeing to receive alimony payments rights in a timely manner for children and adolescents.